Symbiont Types of Scleractinian Corals in Java and Bali Waters, Indonesia - Wijayanti, Diah Permata; Indrayanti, Elis; Haryanti, Dwi; Azizah, Mila Amelia Nur; Bhagooli, Ranjeet (Marine Science Department Diponegoro University, 2025)
Several effects of global warming, particularly coral bleaching, have threatened the symbiotic system of coral reefs. Coral reefs perform a reciprocal system that coincides with coral and their algal symbiont, the environment, and human activities. Nowadays, the system has been threatened by local and global stressors, including global warming. Understanding the ecological resilience of coral reefs to temperature stress relied heavily on the functional variations between algae symbionts as well as their genotypes. Indonesian coral reefs which play a critical value in supporting the reef fisheries, have been reported to experience bleaching events. However, a few reports were on the symbiont type of Indonesian corals. This study investigates the Symbiodiniaceae communities of coral hosts of Panjang Island and Karimunjawa Archipelago in Java Sea, and Tulamben Waters, Bali using internal transcribed spacer two (ITS2) amplicon sequencing. In total, 63 sequences out of 119 coral colonies from 16 genera were obtained from Panjang Island, Karimunjawa Archipelago, and Tulamben waters, Bali. All sequences showed approximately 600 bp in the length of the amplified ITS-rDNA region. The BLAST homology analysis of ITS-rDNA region sequences showed that samples matched Cladocopium sp. and Durusdinium sp. with similarities ranging between 96.79-100%. Cladocopium dominated the symbiont type of the Acropora, and Porites, While Durusdinium is the dominant symbiont in the Pavona, Both algal can be found in Pocillopora sp, Montipora sp, Goniastrea sp., and Lobophyllia sp. The occurrence of the two symbiont types suggests that coral species may adopt heat-tolerant Symbiodiniaceae to adapt to the high environmental temperatures.